KARAKTERISTIK MINERALOGI DAN GEOKIMIA ENDAPAN BAUKSIT TAMBANG TAYAN, KALIMANTAN BARAT - , ASTIKA PRASIDDHA SASYRI W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tayan is one area of West Kalimantan that have a quite big potensial of bauxite. Study area is in Tayan mine area which is part of the mining concession area of PT Antam. The aim of this study is to determine mineralogical and geochemical compositon changes from bedrock into bauxite deposits and factors that influence such processes in that location. Samples consist of fresh rock and laterite deposits taken from 7 different location and then do laboratory analysis like petrographic observation, XRF, XRD, and density test. The factors that influence bauxite lateritization are geomorphology, lithology, and structural geology. Based geomorphological factor, bauxite deposits were formed at very ramp until moderate slopes. From lithology factor, bedrocks in the study area consist of granodiorite, gabbro, and gneiss. Structural geology not exist because intensive rate of weathering. Based on geochemical analysis, laterite deposits consist of clay zone/kong and bauxite zone. XRD analysis results show the transformation of primary minerals such as plagioclase, hornblende, biotite, olivine, pyroxene, microcline, and orthoclase into secondary minerals such as kaolin, halloysite, dickite, nacrite, illite, vermiculite, and pyrophillite. Then, these mineral transform again into alumunium hydroxide minerals like gibbsite, boehmite, and diaspore. Mass balance calculation are used to asses changes in geochemical composition of bauxite deposits using TiO2, P2O5, Y, and Zr as an immobile element. The calculation shows that Al2O3 and FeO is unleached while SiO2 is leached. Bauxite deposits derived from gabbro show 0.25 mass % of SiO2 reduction, 0.19 mass % of Al2O3 enrichment and 0.6 mass % of FeO enrichment. Bauxite deposits derived from gneiss show 0,5 mass % of SiO2 reduction, 2.29 mass % of Al2O3 enrichment, and 1.4 mass % of FeO enrichment. And bauxite deposits derived from granodiorite show 0.45 mass % of SiO2 reduction, 1,4 mass % of Al2O3 enrichment, and 0.73 mass % of FeO enrichment Density test showed that bauxite laterite has a density ranging from 0.9851 to 1.99 gr/cm 3 , while for bedrock ranged from 2.37 to 4.07 gr/cm 3